The effect of Using Educational Stories on developing language skills for first-year primary school students (Open Academia: Journal of Scholarly Research, 2024)
The current investigation aims to investigate the efficacy of educational stories in the development of first-year primary students' linguistic abilities. To accomplish the goals of this research, a quasi-experimental methodology was employed and a set of educational stories was created in addition to a language skills test as a means of research. This test was conducted on a sample of 40 firstyear students in a public school in Iraq that had a large number of women in it. The results of this study demonstrated the value of using educational stories as a powerful educational strategy in the development of language abilities among first-year students, there were significant differences in the scores of students in the experimental and control groups on the language skills test. Based on the aforementioned results, several suggestions were made during the research, including the distribution of the importance of utilizing this.